2017
DOI: 10.15403/jgld.2014.1121.264.kas
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Delayed Ulcer Healing after Endoscopic Submucosal Dissection of Gastric Neoplasms

Abstract: Background & Aims: With improved technology, the size of artificial ulcers after endoscopic submucosal dissection (ESD) has increased. The aim of our study was to examine the risk factors for delayed gastric ulcer healing after ESD, including the possible benefit of potassium-competitive acid blocker (P-CAB) treatment.Methods: The primary outcome was the rate of healing of the artificial ulcers induced by ESD at 8 weeks post intervention. Design: retrospective case series. Setting: Aichi Medical University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 26 publications
1
16
1
1
Order By: Relevance
“…The remaining 23 articles were retrieved for further review, among which 9 were further excluded due to insufficient data for analysis. Finally, 8 full‐text articles and 6 abstracts, with a total of 1328 patients, were included in the final analysis. The flow diagram of study inclusion is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining 23 articles were retrieved for further review, among which 9 were further excluded due to insufficient data for analysis. Finally, 8 full‐text articles and 6 abstracts, with a total of 1328 patients, were included in the final analysis. The flow diagram of study inclusion is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…All of the included studies were carried out in Japan during 2016 and 2018. Among these studies, 7 were retrospectively performed and 7 were prospective RCTs . The duration of drug administration in 2 studies was as short as 2 weeks, whereas those in other studies were at least 4 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Формирование и прогрессирование ГЭРБ и эрозивноязвенных поражений слизистой оболочки гастродуоденальной зоны в значительной мере связано с агрессией содержимого желудка, обусловленной высокой кислотной продукцией [8,9], что объясняет увеличение сочетания поражения пищевода и гастродуоденальной зоны у взрослых пациентов [10]. Основным патогенетическим звеном является нарушение равновесия агрессивных и защитных факторов желудка с мультифакториальным генезом [11][12][13]. Актуальным является вопрос о взаимосвязи ГЭРБ и эрозивно-язвенных заболеваний желудка и двенадцатиперстной кишки в подростковом и особенно в детском возрасте, для которого физиологически характерен более низкий уровень кислотообразования в желудке [14].…”
unclassified
“…The sp e c t r um of VPZ indications has expanded overtime and nowadays it is similar to that of PPIs, including gastroesophageal reflux disease (GERD), gastric and duodenal ulcers healing, management of upper gastrointestinal (GI) bleeding, non-steroidal antiinflammatory drugs (NSAIDs) - submucosal dissection (ESD) [1,3,4]. As to the treatment of GERD, VPZ has been shown to be equally effective as PPIs in various studies using different dosages (5-40 mg) [5,6].…”
mentioning
confidence: 99%